European Association of Urology Guidelines on Non-muscle-invasive Bladder Cancer (Ta, T1, and Carcinoma in Situ) - Babjuk, Marko; Burger, Maximilian; Capoun, Otakar; Cohen, Daniel; Compérat, Eva M; Dominguez Escrig, José L; Gontero, Paolo; Liedberg, Fredrik; Masson-Lecomte, Alexandra; Mostafid, A Hugh; Palou, Joan; van Rhijn, Bas W G; et al. (European urology, 2022)
CONTEXT: The European Association of Urology (EAU) has released an updated version of the guidelines on non-muscle-invasive bladder cancer (NMIBC). OBJECTIVE: To present the 2021 EAU guidelines on NMIBC. EVIDENCE ACQUISITION: A broad and comprehensive scoping exercise covering all areas of the NMIBC guidelines since the 2020 version was performed. Databases covered by the search included Medline, EMBASE, and the Cochrane Libraries. Previous guidelines were updated, and the level of evidence and grade of recommendation were assigned. EVIDENCE SYNTHESIS: Tumours staged as Ta, T1 and carcinoma in situ (CIS) are grouped under the heading of NMIBC. Diagnosis depends on cystoscopy and histological evaluation of tissue obtained via transurethral resection of the bladder (TURB) for papillary tumours or via multiple bladder biopsies for CIS. For papillary lesions, a complete TURB is essential for the patient's prognosis and correct diagnosis. In cases for which the initial resection is incomplete, there is no muscle in the specimen, or a T1 tumour is detected, a second TURB should be performed within 2-6 wk. The risk of progression may be estimated for individual patients using the 2021 EAU scoring model. On the basis of their individual risk of progression, patients are stratified as having low, intermediate, high, or very high risk, which is pivotal to recommending adjuvant treatment. For patients with tumours presumed to be at low risk and for small papillary recurrences detected more than 1 yr after a previous TURB, one immediate chemotherapy instillation is recommended. Patients with an intermediate-risk tumour should receive 1 yr of full-dose intravesical bacillus Calmette-Guérin (BCG) immunotherapy or instillations of chemotherapy for a maximum of 1 yr. For patients with high-risk tumours, full-dose intravesical BCG for 1-3 yr is indicated. For patients at very high risk of tumour progression, immediate radical cystectomy should be considered. Cystectomy is also recommended for BCG-unresponsive tumours. The extended version of the guidelines is available on the EAU website at https://uroweb.org/guideline/non-muscle-invasive-bladder-cancer/. CONCLUSIONS: These abridged EAU guidelines present updated information on the diagnosis and treatment of NMIBC for incorporation into clinical practice. PATIENT SUMMARY: The European Association of Urology has released updated guidelines on the classification, risk factors, diagnosis, prognostic factors, and treatment of non-muscle-invasive bladder cancer. The recommendations are based on the literature up to 2020, with emphasis on the highest level of evidence. Classification of patients as having low, intermediate, or and high risk is essential in deciding on suitable treatment. Surgical removal of the bladder should be considered for tumours that do not respond to bacillus Calmette-Guérin (BCG) treatment and tumours with the highest risk of progression.
Keywords: Intravesical chemotherapy; Radical cystectomy; Humans; Administration, Intravesical; aplikace intravezikální; European Association of Urology (EAU); Urothelial carcinoma; Female; Carcinoma in Situ; Neoplasm Invasiveness; karcinom in situ; lidé; Cystoscopy; ženské pohlaví; Male; nádory močového měchýře; Transurethral resection (TUR); BCG unresponsive; urologie; BCG Vaccine; Bacillus Calmette-Guerin (BCG); Bladder cancer; invazivní růst nádoru; Follow-up; BCG vakcína; mužské pohlaví; Urinary Bladder Neoplasms; Urology; Guidelines; Prognosis; Diagnosis